The natural history of anal cancer-associated human papillomavirus infection among cisgender men and transgender women who have sex with men in an acute HIV cohort in Thailand - Supanat Thitipatarakorn; Sujittra Suriwong; Siriporn Nonenoy; Aphakan Klinsukontakul; Jirat Makphol; Sumitr Tongmuang; Piranun Hongchookiat; Napasawan Chinlaertworasiri; Pravit Mingkwanrungruang; Carlo Sacdalan; Kultida Poltavee; Nitiya Chomchey; et al. (BMC Infectious Diseases)
Abstract Introduction Anal cancer-associated human papillomavirus (caHPV) infection is the leading cause of anal cancer. This study describes human papillomavirus (HPV) progression among participants with acute HIV acquisition. Method Cisgender men and transgender women initiating antiretroviral therapy during acute HIV acquisition (Fiebig 1–5) underwent anal HPV testing at a sexual health clinic in Bangkok from May 2017 to June 2020. Demographic, sexual history, and laboratory data were collected at HIV diagnosis. Two-state Markov models were created to estimate probabilities and durations of HPV 16, 18/45, other caHPV, and any caHPV. Multivariate analyses were performed by adjusting for age and baseline CD4 count. Results A total of 94 participants (median age 26 years) were enrolled. Among 92 participants with valid baseline HPV results, 15.2% had HPV 16, 15.2% had HPV 18/45, 39.1% had other caHPV, and 67.4% had any caHPV at baseline. Over 225.9 person-years (PY), incidence rates were 18.0, 13.9, 44.1, and 82.5 per 100 PY, respectively. Clearance rates were 78.9, 102.9, 93.8, and 56.4 per 100 PY, respectively. Within 2 years of HIV, probabilities of caHPV acquisition were 0.42 for HPV 16, 0.37 for HPV 18/45, 0.82 for other caHPV, and 0.96 for any caHPV. Probabilities of caHPV clearance were 0.91, 0.97, 0.97, and 0.89, respectively. Having ≥ 6 lifetime sexual partners was associated with higher HPV 16 incidence compared to fewer partners (aHR 4.80, 95% CI 1.08–21.37), after adjusting for age and baseline CD4 count. Conclusion Cancer-associated HPV acquisition remains high after acute HIV acquisition and initiation of antiretroviral therapy. Ongoing sexual health consultation, HPV vaccination, and anal cancer screening are necessary for people living with HIV.